(3GdhGaj aj TQM GdYQhV hGdbhGajs - (3eLghds
(3ChdgG (B:s
(3eHJhQ GdChd, hjHOC Hbhdg aj GdebOeI(B: (3GHJZGkA dQVi Gddg GdLejd (B...(3eY Cfj eYJQa HeRLGI GdHVGYI (B...(3eYJeOG aj EJeGe eG bUOJ Ydi cQeg haVdg (B...s
(3BNQgG (B:s
(3eHJhQ GdBNQ, hBNQ GdehLhO efg bhdg(B: (3hGdebJVH ef Jf efgG, hHjGf gPG cdg XGgQ def (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdYQhV hGdbhGajs